PENOLAKAN DISPENSASI NIKAH DAN AKIBAT HUKUMNYA (STUDI KASUS PUTUSAN NOMOR 70/PDT.P/2022/MS.TTN) - Junaidi Berutu; Nila Trisna (LPPM Universitas Ekasakti Padang, 2023)
An application for a marriage dispensation is submitted in order to protect the honor of the family from any behavior that deviates from religious values ​​and applicable legal norms. To avoid greater harm, underage marriage is often the solution to solving problems faced by teenagers who are pregnant out of wedlock. Adjusting to the Marriage Law Number 16 of 2019 concerning Marriage, it explains the age limits for the prospective bride and groom if they wish to enter into a marriage, namely that the prospective husband is at least 19 years old and the prospective wife is at least 19 years old. The Tapaktuan Syar'iyah Court is one of the judicial institutions that has the authority to handle and grant marriage dispensation permits. In 2022 there was one application for marriage dispensation which was rejected by the Tapaktuan Syar'iyah Court, namely determination number: 70/pdt.p/2022/Ms.Ttn. This application was filed by an applicant whose child is 18 years and 10 months old. The applicant wants to marry off his son because he has had a lover for a long time so that there are no undesirable events, so the applicant submits a marriage dispensation to the Tapaktuan Syar'iyah Court. “The authors are interested in researching the stipulation of marriage dispensation Number: 70/pdt.p/2022/Ms because the application was rejected by the Tapaktuan Syar'iyah Court”. The formulation of the problem from this research is what are the judges' considerations in determining the marriage dispensation case Number: 70/pdt.p/2022/Ms.Ttn? and what is the analysis of the consequences of the rejection of the application for marriage dispensation by the judge at the Tapaktuan Syar'iyah Court (Decision Number: 70/Pdt.P/2022/Ms.Ttn).? Analysis of the Consequences of Rejecting an Application for Marriage Dispensation by a judge at the Tapaktuan Syar'iyah Court (Decision Number: 70/Pdt.P/2022/Ms.Ttn). the. The method of this research is field research or empirical juridical method, where the data collection technique for this research is by documentation, namely collecting data related to the determination, and supported by interviews with Judges of the Tapaktuan Syar'iyah Court. Based on the results of this study, it can be analyzed that the Panel of Judges in determining the marriage dispensation case number: 70/pdt.p/2022/Ms.Ttn. using some legal basis. “The legal basis used by the panel of judges is the provisions of Law Number”. 16 of 2019 Concerning Marriage Article 7 paragraph (1) and Compilation of Islamic Law Article 15 paragraph (1). Meanwhile, the judge's consideration in giving the decision to reject the application for marriage dispensation is that the Panel of Judges considers that there is no urgency to enter into a marriage, and there is no information from the applicant's child.